Strategy of Livelihood among Persons Having Social Stigma in Sexual Orientation - Grant Nixon; Mia Siscawati; Juliana Mohd Arpa; Eliza Christabella Phuanerys (JSW (Jurnal Sosiologi Walisongo), 2022)
The dilemma of bisexual identity not only brings existential problems for their identity but also their livelihood. This article focused on the pandemic time and showed the challenges and strategies of Christian bisexual groups to maintain their livelihoods before and after the pandemic. This article aimed to expose the strategy of livelihood among the persons having social stigma in sexual orientation in a heteronormative hegemonic system such as Indonesia. Applying a qualitative method with a case study of two Christian bisexuals, this study showed two main findings: first, gender and bisexual orientation have an impact on rejection, oppression, and job transfer in the period before and after the pandemic due to unequal power relations in heteronormative structures. These power relations also lead to the neglect of non-heteronormative contributions to the informal sector in a heteronormative economic structure. Secondly, bisexual individuals developed a particular resilience strategy during a pandemic, one of which is by utilizing informal networks with non-heteronormative groups. Another finding is the influence of religion which simultaneously provides support and oppression to the livelihoods of non-heteronormative groups.